The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21196986
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training as a Potential Activator of Hippocampal Neurogenesis in the Rat Model of Sporadic Alzheimer’s Disease

Abstract: There is a growing body of evidence that interventions like cognitive training or exercises prior to the manifestation of Alzheimer’s disease (AD) symptoms may decelerate cognitive decline. Nonetheless, evidence of prevention or a delay of dementia is still insufficient. Using OXYS rats as a suitable model of sporadic AD and Wistar rats as a control, we examined effects of cognitive training in the Morris water maze on neurogenesis in the dentate gyrus in presymptomatic (young rats) and symptomatic (adult rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…In these animals, all key signs of the disease develop spontaneously in the absence of mutations in genes App, Psen1, and Psen2 (Kolosova et al 2014;Stefanova et al 2015b;Telegina et al 2019; Kolosova et al 2022). As shown earlier, the rst neurodegenerative changes in OXYS rats occur at the age of 3 months against the background of an increased level of phosphotau (Stefanova et al 2015b;Rudnitskaya et al 2020); already during this period, their learning ability is altered (Burnyasheva et al 2020). In line with their hippocampus-dependent cognitive de cits, OXYS rats show a hippocampal synaptic loss (Stefanova et al 2015a), prominent alterations of synaptic functions (Beregovoy et al 2011;Rudnitskaya et al 2020), signi cant ultrastructural changes (Stefanova et al 2015b, a), and downregulated pre-and postsynaptic proteins (synapsin I and PSD-95, respectively), whose underexpression is considered an indicator event in AD (Stefanova et al 2016).…”
Section: Introductionmentioning
confidence: 62%
“…In these animals, all key signs of the disease develop spontaneously in the absence of mutations in genes App, Psen1, and Psen2 (Kolosova et al 2014;Stefanova et al 2015b;Telegina et al 2019; Kolosova et al 2022). As shown earlier, the rst neurodegenerative changes in OXYS rats occur at the age of 3 months against the background of an increased level of phosphotau (Stefanova et al 2015b;Rudnitskaya et al 2020); already during this period, their learning ability is altered (Burnyasheva et al 2020). In line with their hippocampus-dependent cognitive de cits, OXYS rats show a hippocampal synaptic loss (Stefanova et al 2015a), prominent alterations of synaptic functions (Beregovoy et al 2011;Rudnitskaya et al 2020), signi cant ultrastructural changes (Stefanova et al 2015b, a), and downregulated pre-and postsynaptic proteins (synapsin I and PSD-95, respectively), whose underexpression is considered an indicator event in AD (Stefanova et al 2016).…”
Section: Introductionmentioning
confidence: 62%
“…Recently, in a series of reports [22][23][24], we demonstrated the features of neurogenesis and neurotrophic and glial support of the brain in senescence-accelerated OXYS rats. OXYS rats were derived from the Wistar rat strain (normal healthy rats, control) and are characterized by accelerated senescence.…”
Section: Introductionmentioning
confidence: 98%
“…These neurodegenerative changes in the hippocampus of OXYS rats are accompanied by changes in the extracellular microenvironment of the neurogenic niche rather than by significant direct changes in the formation of new cells in the dentate gyrus (DG) [27]. Recently, we demonstrated that the density of amplifying neural progenitors (ANPs), which give rise to the neuronal cell lineage, is higher in OXYS rats than in Wistar rats during the completion of brain development, and, then, ANP density decreases [22]. Moreover, we showed the altered development of the hippocampus and prefrontal cortex in OXYS rats in an early postnatal period: a disturbance of astroglial support, a microglial deficiency, and a higher intensity of apoptosis during a period critical for the formation of a network among these brain structures [28].…”
Section: Introductionmentioning
confidence: 99%